Crustal Evolution of the Northeast Laurentian Margin and the Peri- Gondwanan Microcontinent Ganderia Prior to and During Closure of the Iapetus Ocean: Detrital Zircon U-Pb and Hf Isotope Evidence from Newfoundland - Willner, Arne; Gerdes, Axel; Massonne, Hans-Joachim; van Staal, Cees; Zagorevski, Alexandre (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Detrital zircon populations in sedimentary rocks from the Laurentian margin and the accreted microcontinent Ganderia on both sides of the main Iapetus suture (Red Indian Line) in central Newfoundland have been studied by combined U–Pb and Lu–Hf isotope analyses. Variation in εHf(t) values with age of zircon populations of distal provenance (>900 Ma) reflect the crustal evolution within the source continents: in zircon derived from Laurentia, episodes of juvenile magma production in the source could be detected at 1.00 – 1.65 and 2.55 – 3.00 Ga, and mixing of juvenile and recycled crust in continental magmatic arcs occurred at 0.95 – 1.40, 1.45 – 1.60, 1.65 – 2.05 and 2.55 – 2.75 Ga. These ages are consistent with the crustal history of northeastern Laurentia. Similarly, zircon of distal provenance from Ganderia reveals times of juvenile magma production in the source at 0.70 – 0.90, 1.40 – 1.75, 1.85 – 2.40 and 2.7 – 3.5 Ga, and episodes of mixing juvenile and recycled crust at 0.95 – 1.35, 1.45 – 1.60, 1.70 – 2.15 and 2.6 – 2.8 Ga. These data reflect the crustal evolution in the present northern part of Amazonia, its likely source craton. The evolution of magmatic arcs at the margins of both continents can be studied in a similar way using detrital zircon having a proximal provenance (<900 Ma). In contrast to the Laurentian margin, Ganderia is characterized by development of Neoproterozoic – Cambrian continental arcs (ca. 500 – 670 Ma) that were built on the margin of Gondwana. εHf(t) values indicate recycling of Neo- and Mesoproterozoic crust. During and following accretion of the various elements of Ganderia to Laurentia, the syn-tectonic Late Ordovician to Silurian sedimentary rocks deposited on the upper plate (composite Laurentia) continued showing only detritus derived from Laurentia. These sedimentary rocks contain detrital zircon from Iapetan juvenile, continental and successor arcs that were active between ca. 440 and 550 Ma, and from continuing magmatic activity until 423 Ma. Arrival of the first Laurentian detritus at the outermost part of Ganderia indicates that the Iapetus ocean was closed at ca. 452 Ma. The magmatic arcs along the former Laurentian margin in Newfoundland evolved differently. In the northwestern part, εHf(t) values point to recycling of Mesoproterozoic and Paleoproterozoic crust. In the southwest, εHf(t) values indicate addition of juvenile crust, recycling of Mesoproterozoic crust and mixing with juvenile magma.